Arm Motor Recovery After Ischemic Stroke: A Focus on Clinically Distinct Trajectory Groups. Issue 2 (April 2021) - Kline, Danielle K.; Lin, David J.; Cloutier, Alison; Sloane, Kelly; Parlman, Kristin; Ranford, Jessica; Picard-Fraser, Matthew; Fox, Annie B.; Hochberg, Leigh R.; Kimberley, Teresa Jacobson
Abstract : Background and Purpose: Recovery of arm function poststroke is highly variable with some people experiencing rapid recovery but many experiencing slower or limited functional improvement. Current stroke prediction models provide some guidance for clinicians regarding expected motor outcomes poststroke but do not address recovery rates, complicating discharge planning. This study developed a novel approach to defining recovery groups based on arm motor recovery trajectories poststroke. In addition, between-group differences in baseline characteristics and therapy hours were explored. Methods: A retrospective cohort analysis was conducted where 40 participants with arm weakness were assessed 1 week, 6 weeks, 3 months, and 6 months after an ischemic stroke. Arm recovery trajectory groups were defined on the basis of timing of changes in the Fugl-Meyer Assessment Upper Extremity (FMA-UE), at least the minimal clinically important difference (MCID), 1 week to 6 weeks or 6 weeks to 6 months. Three recovery trajectory groups were defined: Fast (n = 19), Extended (n = 12), and Limited (n = 9). Between-group differences in baseline characteristics and therapy hours were assessed. Associations between baseline characteristics and group membership were also determined. Results: Three baseline characteristics were associated with trajectory group membership: FMA-UE, NIH Stroke Scale, and Barthel Index. The Fast Recovery group received the least therapy hours 6 weeks to 6 months. No differences in therapy hours were observed between Extended and Limited Recovery groups at any time points. Discussion and Conclusions: Three clinically relevant recovery trajectory groups were defined using the FMA-UE MCID. Baseline impairment, overall stroke severity, and dependence in activities of daily living were associated with group membership and therapy hours differed between groups. Stratifying individuals by recovery trajectory early poststroke could offer additional guidance to clinicians in discharge planning. N/A: (See Supplemental Digital Content 1 for Video Abstract, available at: http://links.lww.com/JNPT/A337 .) Abstract : Supplemental Digital Content is Available in the Text.